MEDIA AUDIO VISUAL DALAM MENGEMBANGKAN KEMAMPUAN KOSA KATA BAHASA PADA ANAK USIA DINI - Rina Rosalina; Agus Sumitra (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2022)
Children's language skills have an important role to be improved by learning to use audio-visual media in developing their language vocabulary skills because at the age of 4-5 years children should not be forced to read. The purpose of learning to use audio-visuals is to make it easier for children to recognize some words by seeing pictures on the screen, hearing sounds by playing fairy tale films so that children can increase their vocabulary, which is a little bit more. In this article the author uses a qualitative descriptive research method which is to analyze, describe, and summarize various conditions, situations from various data collected in the form of the results of interviews or observations about the problems studied that occurred in observations carried out on 13 children and interviews with group teachers. A. The data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study describe the improvement of children's language skills in the learning process with the help of audio-visual media. This research is expected to be a good reference or reference to improve their language skills and also make it easier for children to recognize some letters by looking at pictures that can stimulate intellectually, socially, and emotionally according to their age level.Kemampuan bahasa anak memiliki peranan penting untuk ditingkatkandengan pembelajaran menggunakan media audio visual dalam mengembangkan kemampuan kosa kata bahasanya, dikarenakan pada usia 4-5 tahun anak tidak boleh dipaksakan untuk membaca. Tujuan  dari pembelajaran menggunakan audio visual untuk mempermudah anak mengenal beberapa kata dengan melihat gambar di layar,mendengar suara dengan memutar film dongeng agar anak dapat menambah pembendaharaan kata anak yang sedikit menjadi banyak. Dalam artikel ini penulis menggunakan metode penelitian deskriftif kualitatif yang dilakukan adalah menganalisis, menggambarkan, dan meringkas berbagai kondisi, situasi dari berbagai data yang dikumpulkan berupa hasil wawacara atau pengamatan mengenai masalah yang diteliti yang terjadi di observasi dilakukan terhadap 13 orang anak dan wawancara terhadap guru kelompok A. Analisis datanya dilakukan dengan cara pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini mendeskripsikan peningkatan kemampuan bahasa anak dalam proses pembelajaran dengan bantuan media audio visual.Penelitian ini diharapkan sebagai acuan atau referensi baik untuk meningkatakan kemampuan bahasanya juga mempermudah anak mengenal beberapa huruf  dengan melihat gambar juga dapat menstimulus intelektual, social dan emosional sesuai dengan tingkat usianya.